2020
DOI: 10.3389/fmicb.2020.01363
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities Associated With Long-Term Tillage and Fertility Treatments in a Corn-Soybean Cropping System

Abstract: Tillage and fertilization are common practices used to enhance soil fertility and increase yield. Changes in soil edaphic properties associated with different tillage and fertility regimes have been widely examined, yet, the microbially mediated pathways and ecological niches involved in enhancing soil fertility are poorly understood. The effects of long-term conventional tillage and no-till in parallel with three fertility treatments (No fertilization, N-only, and NPK) on soil microbial communities were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 106 publications
(126 reference statements)
8
47
3
Order By: Relevance
“…This may owe to chisel tillage being less aggressive than typical conventional tillage methods, thus the microbial responses to tillage could be more clear-cut under practices like moldboard plowing [24]. The CT-favored oligotrophs in PC2 and PC3 responding positively to chisel tillage contradicts past studies [27,90], yet these analyses were limited to the phyla level, thereby highlighting the discrepancy between the collective microbial behaviors at higher taxonomic ranks and those of individual microbes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This may owe to chisel tillage being less aggressive than typical conventional tillage methods, thus the microbial responses to tillage could be more clear-cut under practices like moldboard plowing [24]. The CT-favored oligotrophs in PC2 and PC3 responding positively to chisel tillage contradicts past studies [27,90], yet these analyses were limited to the phyla level, thereby highlighting the discrepancy between the collective microbial behaviors at higher taxonomic ranks and those of individual microbes.…”
Section: Discussionmentioning
confidence: 78%
“…Community-level inferences, however, only superficially explain how the soil microbiome responds to CC and tillage. New metagenomics research allows for a closer look into the soil microbial composition and function and the changes brought about by agricultural practices [ 25 , 26 , 27 ]. This usually involves using β-diversity measures to detect shifts in the microbial community structure between samples [ 28 ], interpreting the changes with further analyses targeting specific functional genes, such as amo A, involved in nitrification [ 29 ], and characterizing the compositional shifts that identify the responsive taxa [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tillage can act as a selective pressure leading to a difference in soil microbial community composition under contrasting soil disturbance regimes (Navarro-Noya et al, 2013). Breaking apart soil aggregates exposes previously protected soil organic matter to oxidizing conditions (Six et al, 2000;Van Groenigen et al, 2010) favorable to fast growing copiotrophic bacteria (Srour et al, 2020). However, findings on the effects of tillage on soil microbial communities are not consistent.…”
Section: Differences Between Cropping Systemsmentioning
confidence: 99%
“…A fall in α-diversity under conservation tillage practices is common and attributable to a reduction in evenness as much as in richness (Degrune et al, 2016;Piazza et al, 2019;Tyler, 2019). Nevertheless, conservation tillage and no-till practices favor slower organic matter degradation and the establishment of less diverse but more oligotrophic, complex, and stable microbial communities (Degrune et al, 2017;Song et al, 2017;Wang et al, 2017;Tyler, 2019;Srour et al, 2020). Babin et al (2019) consistently observed a higher abundance of predicted genes involved in oligotrophic lifestyles under low tillage conditions.…”
Section: Impact Of Tillage Practices On Soil Microbiotamentioning
confidence: 97%
“…From a metagenomic perspective, the impact of tilling on soil microbial diversity is usually investigated through αor β-diversity indexes describing respective differences within and between communities. Conventional tillage has a low impact on fungal α-diversity, while increasing prokaryotic αdiversity has a significant impact on prokaryotic β-diversity favoring opportunistic commensal and copiotroph microbes (Degrune et al, 2017;Hartman et al, 2018;Sommermann et al, 2018;Babin et al, 2019;Banerjee et al, 2019;Piazza et al, 2019;Srour et al, 2020). Tilling facilitates fast organic matter decomposition resulting in a sudden nutrient release that is homogeneously distributed in tilled soil columns, thus increasing the abundance of r-strategists or fast-growing microorganisms (Degrune et al, 2017;Schmidt et al, 2018).…”
Section: Impact Of Tillage Practices On Soil Microbiotamentioning
confidence: 99%